Nutrient utilisation and enteric methane emissions in female Sahiwal calves of varying residual feed intake - Dudi, Kuldeep; Datt, Chander; Mohini, Madhu; Devi, Indu; Sharma, V K; Kundu, S S; Singh, Sohan Vir (Indian Journal of Dairy Science, 2016)
Residual feed intake (RFI) is the difference between actual feed intake and predicted feed intake for the animal. The study was conducted with Sahiwal female calves (n=18) of average age 9 months and body weight (BW) 77.97Â±2.82 to determine RFI value for individual animals and correlate it with nutrient utilization and enteric methane emissions. Experimental animals were fed in form of TMR (Concentrate: Roughage= 40:60) for 120 days including adaptation period of 22 days and RFI value for individual animals were calculated using regression equation and they were designated as low (n= 9; RFI= -0.14 kg/ d) and high (n= 9; RFI= +0.14 kg/d) RFI groups. Low RFI group showed better feed conversion ratio (FCR) compared to high RFI group (5.52 and 6.64 kg DM consumed/kg gain). FCR value was 20.29% lower in low RFI group with low RFI group consuming less (P